Determination of LDL cholesterol levels in cattle comparing two methods - Osorio, José Henry (2018)
The aim of this study was to compare the direct method with the precipitation method for the determination of LDL cholesterol in a species with a metabolic HDL pattern. Blood samples were taken from 56 dairy cows early in the day. The LDL cholesterol levels were determined in the serum by both methods using commercial kits. The results were statistically analyzed using a one-way analysis of variance. The direct method reported values (mg/dl) of 46.66, 6.50, 101.83, 95.33 and 24.15 for average, minimum, maximum, range and standard deviation, respectively, and using the precipitation method values (mg/dl) of 14.33, 0.36, 59.12, 58.76 and 11.21 respectively, with a statistically significant difference between these methods for a 95.0% confidence level. The results indicate that the direct method is the most reliable for the determination of LDL cholesterol levels.